MEMBANGUN KECERDASAN EMOSIONAL DAN ADVERSITI (EMOTIONAL AND ADVERSITY INTELLIGENCE) PENDIDIK DAN TENAGA KEPENDIDIKAN PENDIDIKAN NON FORMAL (PTK-PNF) - Widya Ayu Puspita (JIV-Jurnal Ilmiah Visi, 2008)
The educators and the administrative personnel of non-formal education play as frontliners in implementing the programs of non-formal and informal education. They are expected to provide learning communities with excellent services. On the other hand the existing problems are very complicated and need high skills to solve. This article discusses emotional and adversity intelligence and how to develop them for the educators and the administrative personel of non-formal education.